Triple Therapy in COPD: Can We Welcome the Reduction in Cardiovascular Risk and Mortality? - Solidoro, Paolo; Albera, Carlo; Ribolla, Fulvia; Bellocchia, Michela; Brussino, Luisa; Patrucco, Filippo (Frontiers in Medicine, 2022)
Chronic obstructive pulmonary disease (COPD) is a complex disease which consists in the reduction of the airflow and leads to the disruption of the pulmonary tissue due to a chronic inflammation. The progression of the disease is characterized by an exacerbation of the symptoms and the presence of life-threatening systemic complications, such as stroke and ischemic heart disease, with a progressive decline in lung function which can deeply impact the quality of life. Mortality represents the most important COPD outcome, with an increased risk in patients with cardiovascular comorbidities. The efficacy and safety of triple inhaled therapy were demonstrated by numerous controlled trials. Above all, many robust data are now available on the effectiveness of the triple therapy to reduce mortality in COPD patients.